Features of Risk Stratification, Diagnosis and Secondary Prevention in Patients with Multifocal Arterial Disease. Part 2: Treatment Options - V. G. Grachev; S. S. Vedenskaya; O. G. Smolenskaya (Рациональная фармакотерапия в кардиологии)
The similarity of the pathogenesis of atherosclerosis and atherothrombotic complications, regardless of their location, makes the approaches to secondary prevention similar, which include lifestyle modification, pharmacotherapy of hemodynamic disorders, metabolic changes and hemostasis. Secondary prophylaxis in patients with multifocal arterial lesions using antihypertensive, antithrombotic and lipid-lowering therapy provides a more pronounced decrease in the incidence of cardiovascular complications than in lesions of single vascular lesions due to a higher initial risk. However, these treatments do not reduce the risk to the level that is achieved by treating patients with less atherosclerotic lesion. In this regard, it is of interest to use the currently available new methods and regimens of drug therapy in patients with multifocal arterial lesions, which make it possible to more intensively influence the mechanisms of atherosclerosis progression and more effectively prevent the development of its complications.